Acceptability and feasibility of telehealth outpatient video‐link consultations: A national cross‐sectional survey of surgeons prior to the COVID‐19 pandemic. (3rd November 2022) - Mackenzie, Lisa; Noble, Natasha; Proietto, Anthony; Jones, Julia; Norton, Grace; Palazzi, Kerrin
Abstract: Objective: This study explored use and perceived barriers to the use of post‐operative video‐link telehealth among a sample of Australian surgeons shortly before the COVID‐19 pandemic. Methods: During 2019–2020, a survey was mailed to RACS or RANZCOG Fellows. Design: Cross‐sectional survey. Setting and Participants: A total of 907 surgeons practising in Australia completed the survey. Main Outcome Measures: The study‐specific survey assessed telehealth use in the last 3 months and the perceived barriers and enablers to the use of post‐operative teleconsultations, across the domains: quality of care; convenience and efficiency; legal/regulatory issues; financial issues and technological issues. Results: Twenty‐five percent of eligible surgeons returned the survey, with n  = 763 pre‐pandemic responses included in analyses. Approximately one‐quarter (26%) of surgeons had used telehealth post‐operatively with patients in the last 3 months. The most frequently endorsed barriers to use related to quality of care: 'I cannot undertake a patient examination' and 'I cannot provide the same level of care as during an in‐person consultation'; and convenience and efficiency: 'Teleconsultations are more difficult to arrange'. Surgeons who had recently used telehealth were less likely to endorse most barriers. Younger age, awareness of Medicare telehealth reimbursement and working in neurosurgery, urology, paediatric surgery and plastic and reconstructive surgery (compared to general surgery) were associated with recent telehealth use by surgeons. Conclusions: Some surgeons' perceived barriers to telehealth pre‐COVID may be overcome by COVID‐19‐related telehealth uptake and familiarisation. However, many barriers will need to be addressed to ensure that telehealth adoption is sustained beyond the pandemic.